The Effect of Thiazolidinediones and SGLT-2 Inhibitors on Minerals,VIT.D3, Blood Glucose and Weight Gain in Wistar Rats Induced with Type 2 Diabetes - Shaimaa Adnan Abd Alhussien Alshmmari, Suaad Mohammad Joda Al-Hadrawy, (Pakistan Journal of Medical & Health Sciences, 2022)
Type 2 diabetes mellitus and osteoporosis are among the most common health problems around the world. Diabetes is usually associated with increase a risk of bone fracture, Recent studies has indicated the harmful effects of some of anti-diabetic drugs on bone metabolism. Therefore, the goal of this study was to investigate the effect of two types of anti-diabetic drugs: Thiazolidinediones (TZDs) (30 mg/kg) and sodium-glucose cotransporter-2 (SGLT-2) inhibitors (10 mg/kg) on Vit.D and bone minerals on serum of laboratory female rats induced with type 2 diabetes mellitus. The study was conducted on animals Faculty of science/ Department of biology/University of kufa. And Central Laboratories/ In Medical City. during the period from 27 october 2021 till the end of 22 February 2022. Thirty-two adults female Albino rats (Rattus norvigicus) were randomly divided to two main groups of sixteen animals, The first group was treated for a period of 2 weeks and the second group was treated for a period of 2 months. Each group of them was divided into secondary four groups of four rats including: a control (Co1 and Co2) were fed regular rats pellet, the second group (HFD 1 and HFD 2) were fed with high fat diet (42% lipid, 32%g sucrose, 14% protein), the third group were fed with high fat diet and treated with TZDs (30 mg/kg) and fourth group were fed with high fat diet and treated with SGLT-2i (10 mg/kg). After the end of the treatment period, which is two weeks and three months, the blood was drawn using a method of cardiac puncture technique for estimation of blood glucose, bone minerals in serum which include (calcium, magnesium, inorganic phosphate) and serum Vit.D3 concentration. Body weight gain was significantly increased (p≤0.05) in animals treated with HFD high-fat diet (uncontrolled diabetic group) and in animals treated with TZDs compared to the control and animals treated with SGLT-2i. Also, the results of this study showing a significant increase (p£0.05) on blood glucose in animals fed with HFD compared with other groups and there was a significant decrease (p£0.05) in blood glucose in animals group treated with TZDs and SGLT-2i compared with HFD. The diabetic induced group (HFD group) treated for two months showed a significant decrease (p≤0.05) in vitamin D3 concentrations. The results of calcium concentrations in the blood showed a significant decrease (p≤0.05) in calcium concentration in the group induced with diabetes and the group treated with TZDs for two months compared to other groups. With regard to magnesium concentrations, the results showed a significant decrease (p≤0.05) in the group induced with diabetes and the group treated with TZDs for two months compared to other groups. While there was a significant increase (p≤0.05) in the concentrations of magnesium in the group treated with SGLT2i for two months compared to other groups. Also, the results showed a significant increase in the concentrations of serum inorganic phosphate in the groups treated with high-fat diet (diabetic induced group) for two months and the group treated with SGLT2i for two months, compared to the control group and the groups treated with TZDs. In conclusion: Uncontrolled diabetes mellitus has adverse effects on the concentrations of Vit.D3 and bone minerals. Also, Long-term treatment with Thiazolidinedionse (TZDs) and SGLT-2 inhibitors, despite its control of blood sugar has harmful effects on bone minerals and Vit.D3.